REVIEW PAPERSHypertrophic scars and keloids Part I. Pathogenesis and pathomechanism - Witmanowski, Henryk; Lewandowicz, Edward; Zieliński, Tomasz; Łuczkowska, Magdalena; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Aberrant wound healing manifests in formation of hypertrophic scars or keloids. The aim of this paper is to present, according to a new paper, current information about pathogenesis, clinical manifestation and normal and aberrant scar formation. It seems to be a very important problem, especially for plastic surgeons. Hypertrophic scars and keloids are a cause of dissatisfaction and lead to functional and cosmetic deformities, stress and discomfort in treated patients. A knowledge of the differences between hypertrophic scars and keloids and pathomechanism may be very useful in prevention and selection of a proper therapeutic approach.